Cyclin-dependent kinase 4 and 6 inhibitors (CDK4/6i): Mechanisms of resistance and where to find them - L. Foffano; L. Cucciniello; E. Nicolò; I. Migliaccio; C. Noto; C. Reduzzi; L. Malorni; M. Cristofanilli; L. Gerratana; F. Puglisi (Breast)
CDK4/6 inhibitors (CDK4/6i) have significantly impacted on the treatment of HR + HER2 negative (HER2-) metastatic breast cancer (BC) when combined with endocrine therapy. Nonetheless, despite significant research efforts, the mechanisms of de novo and acquired resistance to CDK4/6i have not yet been fully elucidated, highlighting the need for a deeper understanding of these process. Additionally, the importance of dissecting CDK4/6i resistance from endocrine resistance for personalized treatment is increasingly recognized.Liquid biopsy has emerged as a minimally invasive tool for identifying circulating biomarkers of resistance through the integration of multiparametric and dynamic assessments that encompass ctDNA, CTCs, exosomes, and epigenetic ctDNA alterations, representing a promising perspective for the clinical characterization of treatment resistance and guiding post-progression strategies to improve patient outcomes.Aim of this review is summarize potential mechanisms of CDK4/6i resistance, along with the advantages of using liquid biopsy to identify resistance biomarkers in HR+/HER2- MBC patients treated with CDK 4/6 inhibitors.